The Influence of Self-Management Techniques on The Learning Discipline of Class VIII Students at Frater Don Bosco Middle School, Tarakan - Aprina Aprina; Ni Made Diah Padmi; Siti Rahmi (Journal of Social Science and Economics (JOSSE), 2025)
This study aims to determine the effect of self-management techniques on the learning discipline of eighth-grade students at Frater Don Bosco Middle School, Tarakan. Learning discipline remains a significant obstacle in the school environment. Self-management techniques were chosen as an intervention because they can train students to manage their time, behavior, and learning responsibilities independently. This study used a quantitative approach with a quasi-experimental design of the nonequivalent control group type. The sample consisted of two classes, namely the experimental class and the control class, which were selected using a purposive sampling technique. The instrument used was a learning discipline questionnaire. The results showed a significant increase in student learning discipline after being given self-management treatment, compared to the control class. This finding indicates that self-management techniques have a positive effect on improving student learning discipline. The implication of this study is the importance of implementing self-management strategies in the learning process to support optimal student academic achievement.